Estimation of plasma volume changes during marathon running. Issue 3 (September 1985) - Maughan, R J; Whiting, P H; Davidson, R J
Abstract : Indices of fluid loss have been compared in 47 male runners who completed a competitive marathon (42.2 km) race in times varying from 2 hr 37 min to 4 hr 51 min. Body weight was recorded before and after the race; venous blood samples were collected shortly before and immediately after the race and used for the estimation of haemoglobin concentration, packed cell volume and serum concentration of albumin and total protein. All runners drank a total of 1.4 L of water during the race. The mean decrease in body weight was 2.1 +/- 0.8 kg (mean +/- SD), corresponding to 3.0 +/- 1.1% of initial weight. The decrease in plasma volume (PV), calculated from the haematological parameters, was 6.5 +/- 7.8% (P less than 0.001). Serum total protein concentration increased (P less than 0.001) by 10.4 +/- 4.8% and serum albumin (P less than 0.001) by 9.6 +/- 5.6%. The increase in serum protein concentration was correlated (r = 0.64, P less than 0.001) with the calculated decrease in PV, but was greater (P less than 0.001) than could be accounted for by the loss of plasma water. The change in PV varied widely between individuals and was unrelated to running speed. The estimated decrease in total body water (5%) was not different from the decrease in PV (6.5%), suggesting that water losses were evenly distributed between the intracellular and extracellular compartments.